Analisis Yuridis Pemberian Hibah Kepada Pejabat Ditinjau Dari Tindak Pidana Gratifikasi - Viola Audy; Hery Firmansyah (UNES Law Review, 2023)
Humans are social creatures who need each other to interact and carry out activities. In their daily life, humans are accustomed to doing something so that from this habit, laws are born that are agreed upon by the local community where the law was born. Because with the development of the times and the massive growth of humankind that is increasingly expanding, a law is needed that will become the single rule for all of society. Laws are made to provide protection and a sense of security for the community, but in some cases even though there are laws there are still those who commit criminal acts such as corruption. So it is necessary to have laws that regulate corruption at this time, because as technology develops, the modus operandi of corruption becomes more sophisticated. One of the efforts of criminal acts of corruption is giving gifts or grants to officials which is called gratuity. This study uses a type of qualitative research that examines and analyzes legal materials from relevant literature. The difference between gratuities and grants is needed is to avoid a legal vacuum or legal uncertainty, it will be difficult to ensnare corruptors into criminal acts, because basically grants are part of civil law making it difficult to fulfill elements of corruption. However, corruption through grants can be said to be gratification if it is given to state administrators and does not report the results of receiving the grant.